EFFECTIVENESS OF THE VILLAGE FINANCIAL SYSTEM APPLICATION (SISKEUDES) AT THE PEMATANG VILLAGE OFFICE, BANUA LAWAS DISTRICT, TABALONG REGENCY - Selamat Riadi; Erwin Maulana; Novita Azizah (Journal of Social Science, 2025)
Objective: This study examines the effectiveness of the Village Financial System Application (SISKEUDES) in supporting transparent, accountable, and efficient village financial management at the Pematang Village Office, Banua Lawas Sub-district, Tabalong Regency, while also identifying influencing factors and improvement efforts. Method: A descriptive qualitative approach was employed using interviews, observations, and document analysis, with purposive sampling involving nine informants. Data were analyzed through systematic stages of data reduction, data display, and verification to ensure analytical rigor. Results: The findings indicate that SISKEUDES has generally been implemented effectively across key dimensions, including program success, target achievement, operational procedures, efficiency, output quality, and overall goal attainment. However, effectiveness has not been fully realized in terms of program satisfaction related to infrastructural needs, particularly unstable internet connectivity. This limitation directly affects system performance and user convenience. To address this constraint, the village government introduced supporting measures, such as procuring additional Wi-Fi modems, alongside recommendations for continuous training and human resource strengthening. Novelty: This study contributes original empirical insights by integrating Campbell’s effectiveness framework with a contextual analysis of digital public finance governance at the village level, highlighting infrastructure readiness as a critical determinant of e-government effectiveness in rural administration.